(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
The experiment was designed to determine the protective role of pomegranate seed oil on lung function and tissue against cadmium chloride toxicity. In this experiment, 20 animals (rabbit females) were used. Lung efficiency was measured by measuring the size of red blood cells and hemoglobin, as well as studying the histological effects of cadmium chloride against lung tissue and the protective role of pomegranate seed oil . The results showed that the treatment of animals with cadmium chloride at a dose of 5 mg / kg bw for 30 days led to a significant increase in packed cell volume (PCV) and hemoglobin (Hb) compared to control group . The treatment of animals with cadmium chloride has also shown that there is no possibility of distinguishing the alveolar of lung (AV) with the presence of focal infiltration of the inflammatory cells with a marked thickening of the wall of the blood vessel (TW) with blood congestion (CON) Pomegranate seed oil improves most of the negative effects caused by cadmium chloride .